Competition and banking sector stability in Kenya - Faith Atiti; Raphael Agung; Stephanie Kimani (Kenya Bankers Association (KBA), 2020)
Financial liberalization and globalization have enhanced competition in the banking sector with profound implications for stability. Positively, competition has had obvious benefits including increased efficiencies, continuous financial innovations and accelerated financial inclusion. However, to certain levels, competition may increase risk taking by banks where charter value is threatened. To this end, the assumption that efficiency and competition consideration may have eclipsed financial stability concerns in the run up to the global financial crisis has raised questions on the actual linkage between stability and competition, with increased calls for more nuanced approach to the assessment. This paper analyses the competition-stability nexus within the Kenyan context using quarterly data from 23 banks operating in the country between 2006 and 2018. The empirical estimation follows a three-step model. First, we construct a composite Bank Stability Index, building on the Uniform Financial Rating System Model that incorporates capital adequacy, asset quality, earnings and liquidity measures in the Bank stability estimate. Secondly, a proxy for bank competition is computed using the Panzar-Rosse H-statistic. Finally, we regress the Bank Stability Index against competition as measured by the H-Statistic, controlling for business cycles and some bank specific features including efficiency. The empirical results show a negative relationship between competition and bank stability. However, the relationship is not statistically significant. This underlines the need for an effective regulatory and supervisory environment that ensures stability even as the banking landscape grows increasingly competitive. This may include proactive policy measures that can counter the adverse effects of changes in banking competition on the sector's stability.
Keywords: 330; Bank; Wettbewerb; Bankenliquidität; Kenia